Foreign Electoral Interference Normative Implications in Light of International Law, Human Rights, and Democratic Theory - Reimann, Nils (sui generis Verlag, 2023)
Foreign interference in elections may have attracted increased public attention since 2016, but it is a practice virtually as old as modern electoral democracy itself. This book offers the most comprehensive account of its normative implications yet. It discusses relevant standards of international law, human rights, and democratic theory, thereby casting a net wide enough to address the fundamental value of human dignity as well as the conditions of real political autonomy. Ultimately, the book identifies potential deficits of legality, accountability, and legitimacy ensuing from certain types of foreign electoral interference, and it provides ideas on what can and should be done in response.